Chicago Works : Art from the Windy City - Fernandes, Joyce; Bruce Gallery, Edinboro University of Penssylvania, Philadelphia (Erie : Erie Art Museum, 1989)
Banicki, Michael ; Faber, Mindy ; Fish, Julia ; Gerber, Gaylen ; Itatani, Michiko ; Klepper, E. Daniel ; Kybartas, Stashu ; Labus, Paul ; Lostutter, Robert ; Mellinger, Jeanine ; Metrick, Robert ; Morris, Darrel ; Phillips, Tony ; Ploof, John ; Ramberg, Christina ; Rezac, Richard ; Rogala, Miroslaw ; Schneller, Ian ; Sigler, Hollis ; Simpson, Diane ; Snyder, Bob ; Stoppert, Mary ; Warneke, Ken ; Wharton, Margaret
Chicago Works: Art from the Windy City, Bruce Gallery, Edinboro University of Penssylvania, Erie Art Museum, Art Works, March 1 - April 15, 1989
boek
Keywords: Chicago